Physics Education Technology Project (PhET): Interactive Simulation to Improve Students' Understanding of Concepts and Perceptions - Dian Samitra; M. Lutfi Firdaus; Yuni Krisnawati (Jurnal Paedagogy, 2023)
This study aims to analyze 1) the effect of PhET Gene Expression on students' conceptual understanding and 2) students' perceptions of the Gene Expression Essentials simulation. The research method used was Quasi Experiment with a quantitative approach. The research design used a one-group pretest-posttest design. In the treatment phase, students learned using gene expression simulations from PhET simulations. Data on students' understanding of concepts were obtained from tests and perceptions using a questionnaire. Data analysis used the t-test with the help of SPSS 23 and descriptively. The Paired sample t-Test analysis results showed that the significance was 0.000 <0.05. Students stated that PhET in motivation, effectiveness, benefits, and presentation had high interpretations. Based on the research that has been done, PhET Gene Expression Essentials influences students' understanding of concepts, and students respond positively to PhET Gene Expression Essentials.